Efficient in-line skyrmion injection method for synthetic antiferromagnetic systems - Gan, Wei Liang (2018)
Although it has been proposed that antiferromagnetically-coupled skyrmions can be driven at extremely high speeds, such skyrmions are near impossible to inject with current methods. In this paper, we propose the use of DMI-induced edge magnetization tilting to perform in-line skyrmion injection in a synthetic antiferromagnetic branched nanostructure. The proposed method circumvents the skyrmion topological protection and lowers the required current density. By allowing additional domain walls (DWs) to form on the branch, the threshold injection current density was further reduced by 59%. The increased efficiency was attributed to inter-DW repulsion and DW compression. The former acts as a multiplier to the effective field experienced by the pinned DW while the latter allows DWs to accumulate enough energy for depinning. The branch geometry also enables skyrmions to be shifted and deleted with the use of only three terminals, thus acting as a highly scalable skyrmion memory block.